Sorghum-Soybean Flour Enteral Formula Reduces Blood Glucose, Cholesterol, Triglycerides, LDL, and Increases HDL and Albumin in Hyperglycemic Rats - Probosari, Enny; Dewi, Suci Noviya; Alfadila, Tsania Izza; Handayani, Endah Nur; Rizkita, Maura Sania; Candra, Aryu; Ardiaria, Martha; Puruhita, Niken; Murbawani, Etisa Adi (Cell and BioPharmaceutical Institute, 2025)
Background: Diabetes mellitus prevalence is rising. Liquid feeding in the form of enteral formulas is needed to meet the nutritional needs of patients who cannot consume orally. The development of enteral formulas based on sorghum-soybean flour for diabetes mellitus patients, which has been nutritionally analyzed and adjusted to the requirements of enteral manufacturing, was selected for further in vivo research. This study evaluated the effect of the sorghum-soybean flour formula on fasting blood glucose (FBG), lipid profile levels, and albumin in hyperglycemic rats.Materials and methods: This was a true experimental study with pre–post-test randomized control design. Wistar rats were divided into four groups: negative control group was normal rats and given standard feed only; positive control group was hyperglycemic rats and given standard feed only; treatment (T)1 and T2 groups were hyperglycemic rats given standard feed along with enteral formula at a dose of 4,41 g/day and 5,51 g/day for 28 days. Blood samples were collected to analyze FBG, albumin, low-density lipoprotein (LDL), high-density lipoprotein (HDL), triglycerides, and total cholesterol.Results: There were differences in the levels of FBG, albumin, LDL, HDL, triglycerides, and total cholesterol before and after the intervention in groups T1 and T2. Group T1 showed an 8.12% decrease in FBG, while T2 showed a 29.89% decrease. Triglycerides decreased by 29.22% in T1 and 31.85% in T2; cholesterol decreased by 11.41% in T1 and 13.94% in T2. LDL levels decreased by 29.97% in T1 and 38.44% in T2. Albumin levels increased by 47.90% in T1 and 56.67% in T2. HDL levels increased by 23.94% in T1 and in 35.04% in T2.Conclusion: Administration of an enteral formula based on sorghum-soybean flour can reduce FBG, triglycerides, total cholesterol, and LDL levels, and increase albumin and HDL levels in hyperglycemic rats.Keywords: hyperglycemia, enteral formula, albumin levels, fasting blood glucose, HDL, LDL, total cholesterol, triglycerides